Perfil de segurança fetal dos principais grupos farmacológicos utilizados no tratamento de doenças reumáticas inflamatórias - Falcão, Sandra Isabel Salvador (2007)
The high prevalence of inflammatory rheumatic diseases in women of childbearing age increases the risk of exposure to antirheumatic agents during conception, pregnancy and breast feeding. The decision for pharmacological treatment initiation/ maintenance should be the result between the severity of maternal disease and the risk/benefits with treatment. The aim of this paper was to review recent literature about drug fetal safety profile, strength the importance of monitoring the pregnancy in patients with inflammatory rheumatic diseases and stress the need for further research in this area.